Avaliação da marcha e do equilíbrio em pacientes portadores de síndrome lipodistrófica secundária à terapia antirretroviral - LIMA, Ramon Costa de (Universidade Federal do Pará, 2017)
The Acquired Immune Deficiency Syndrome (AIDS ) is a disease that devastates the world's population decades and hear this diagnosis was like a " death sentence " . With the advent of new drug therapies, characteristic of the acute disease has become a chronic condition . However , the drugs used in antiretroviral therapy (ART ) have adverse reactions , especially when the patient is subjected to long-term use of so-called "cocktail " . One of the side effects of ART is lipodystrophy , which causes the molecular scale adpócitos apoptosis and mitochondrial alterations in the muscle fibers . Thus, the objective of this study was to investigate the effects of muscle Lipodystrophy and changing patterns of gait and balance of patients in this clinical contexto. Were evaluated 38 subjects of both sexes, divided into two groups: HIV positive with lipodystrophy (HIVL) and HIV positive without lipodystrophy (HIV). The balance test was used a force platform (EMGSystem of Brazil), which evaluates the displacement of the pressure Center (Cop) in the anteroposterior directions (AP) and mediolateral (ML) of the individual generating the variables the total linear displacement, total area of displacement and displacement velocity amplitude of the displacement at a time of sixty seconds for each collection. For the gait test we used the 8-channel Electromyograph (EMGSystem of Brazil) to capture the electrical signals of the muscles Rectus Femoral (RF), biceps femoral (BF), gastrocnemius Lateral (GL), anterior tibialis (TA) and Gluteus Médius (GMD) during ambulation and processing of electromyographic signal was made through the mathematical model Root Mean Square (RMS), and normalized by maximum voluntary contraction (MVC). The results of each group were expressed as mean and standard deviation and compared using the Student t test for parametric samples and the Mann-Whitney test for nonparametric samples. Analysis of the results in the two phases of the gait cycle showed significant differences. In the phase of support and swing phase electromyographic signals of GMD and TA muscle were higher in HIVL group for HIV group. As for the balance variables with statistical significance when comparing the groups were the total displacement and displacement area, both higher in HIVL group for HIV group. Thus we conclude that patients with lipodystrophy syndrome showed changing patterns of gait and balance.